Relationships between tyrosine, phenylalanine, chlorogenic acid, and ascorbic acid concentrations and blackspot biochemical potential and blackspot susceptibility in stored russet potatoes. (22nd February 2018) - Goyer, Aymeric; Pellé, Julien
Abstract: BACKGROUND: Blackspot in potato is an internal tissue discoloration that occurs during handling and transport of potato tubers. Blackspot is cosmetically undesirable and represents a huge economic cost for the potato industry. The aim of this study was to test whether concentrations of certain metabolites in the potato tuber cortex could predict blackspot susceptibility. RESULTS: Seven russet potato varieties were stored for eight months at 8.8 °C. Stored tubers were subjected to mechanical impact and evaluated for blackspot susceptibility. A blackspot susceptibility index was calculated for each variety by determining an index for the percentage of the tuber cortex area that was covered with blackspot, and an index for the intensity of blackspot discoloration. Concentrations of tyrosine, chlorogenic acid, phenylalanine, and ascorbic acid, and blackspot biochemical potential of tubers to synthesize pigments were measured in the tuber cortex. Blackspot indices, metabolites concentrations and blackspot biochemical potential varied significantly between varieties. Tyrosine concentrations strongly, significantly, and positively correlated with blackspot biochemical potential. Phenylalanine concentrations showed good, significant, and positive correlation with blackspot biochemical potential and discoloration index. None of the analyzed metabolites correlated with blackspot susceptibility. CONCLUSION: Concentrations of tyrosine and phenylalanine explained up to ∼80% of the variation in blackspot biochemical potential between varieties but did not correlate with blackspot susceptibility. © 2018 Society of Chemical Industry